Aktifitas Antifungi Daun Ketepeng Cina (Cassia alata L.) Fraksi Etanol, N-Heksan, dan Kloroform terhadap Jamur Microsporium canis - Mathlail Fajri; Nurul Marfu'ah; Lija Oktya Artanti (University Of Darussalam Gontor, 2018)
Plants created by Allah have many benefits. One plant that is widely used is Cassia alata L. Traditionally, the leaves are often used as an anthelmintic, ulcers, constipation, and skin diseases. Based on community experience, antifungal activity was investigated with ethanol, chloroform, and nhexane fraction of Cassia alata leaves to inhibit Microsporum canis, one of the dermatophyte fungi that causes tinea diseas. This study was an experimental study using a fraction of ethanol, chloroform and n-hexane Cassia alata were tested on Microsporum canis with a concentration of 12.5%, 22.5%, 32.5% and 42.5%. The results showed that the fraction of ethanol, chloroform, and n-heksan Cassia alata, has antifungal activity against Microsporum canis. The fraction that has the highest activity to inhibit the growth of Microsporum canis is the fraction of ethanol at a concentration of 42.5%, compared to the other two fractions and positive controls, generate inhibitory diameter of 27.88 mm (12.5%), 41.25 mm (22.5%), 48 mm (32.5%), 62 mm (42,5%). Phytochemical screening results indicate the presence of secondary metabolites content in each fraction, Secondary metabolites contained in the ethanol fraction are alkaloids, flavonoids, tannins, saponins and terpenoids, while in the chloroform fraction tannins, saponins, alkaloids, and flavonoids, and n-hexane fractions contain, alkaloids, saponins, tannins, and terpenoids.